Photoelectrocatalytic Degradation of Dyes by Titanium Dioxide Thin Films Prepared via Thermal Oxidation and Electrodeposition - Chong , Alvin Jing Kai (2009)
Titanium dioxide (TiO2) thin film electrodes were prepared using two techniques which were cathodic electrodeposition and thermal oxidization of titanium plates. The characteristic of TiO2 electrodes were analysed using X-Ray Diffractometry (XRD), Field Emission Scanning Electron Microscopy (FESEM) and UV/Vis Spectroscopy. TiO2 anatase and rutile phase structure was found in electrodeposition TiO2 thin film after heat treatment whereas only rutile phase was observed for thermal oxidation TiO2 thin film. Electrodeposited and thermally oxidized TiO2 electrodes showed the highest photosensitivity after calcination at 600 ºC and 700 ºC respectively when analysed using Linear Sweep Photovoltammetry (LSPV) technique. Photoelectrochemical degradation of dyes was carried out in a 3 electrode system reactor where the working electrode was TiO2 thin film under illumination of a light source for 2 hours. The removal of dyes was investigated by monitoring dyes decolourisation rates using UV/Vis Spectroscopy. The photoelectrochemical degradation studies of Chicago Sky Blue 6B (CSB) dye was studied varying the initial dye concentrations, applied potentials and supporting electrolytes. The effect of repeated usage, light sources and changing removal methods were also examined. Photoelectrocatalytic degradation system for both TiO2 thin film electrodes achieved better removal of CSB dye than in photocatalytic system. Thermal oxidized TiO2 electrode gave faster removal rate compared to electrodeposited TiO2 electrode in photoelectrocatalytic degradation of CSB dye. The removal of CSB increased with the increased of external applied potential from 0 V to 1.5 V versus Ag/AgCl reference electrode in both TiO2 thin film electrodes. The kinetic data at different applied potential fitted well to first-order kinetic model. TiO2 thin film electrodes showed its best photoelectrocatalytic degradation under illumination of UV light. The removal percentages of 5 times repeated usage for thermal oxidized TiO2 electrode showed insignificant differences. However, the removal percentages of CSB decreased when electrodeposited TiO2 electrode was used repeatedly for 5 times. The photoelectrocatalytic removal efficiency of CSB was compared with two different dyes which are Methyl Orange (MO) and Methylene Blue (MB). The removal of MO was higher than in CSB whereas the removal of MB was the lowest for both TiO2 electrodes.